Proceso de ASC - AGENDAS DE GENERO Y PLANES DE DESARROLLO. MEDELLIN 2004-2019 (2020)
The project analyzes the inclusion of gender agendas in the Municipal Development Plans of the city of Medellín during four administrations, spanning the period 2004-2019. The methodology used was descriptive and exploratory through a literature review focused on the Plans. Among the main findings is an increase in the budget allocated to gender issues with each new Administration, as well as the expansion of the concept of gender from an exclusively female issue to other population groups such as the LGBTIQ + population. Among the conclusions, it is worth highlighting the significant progress in the establishment of ADG in the PDM as a central instrument for city construction and the need to increase the number of resources and percentage of the total PDM budget allocated to ADG-related programs.